2022
DOI: 10.1002/adfm.202210123
|View full text |Cite
|
Sign up to set email alerts
|

Neuro‐Glia‐Vascular‐on‐a‐Chip System to Assess Aggravated Neurodegeneration via Brain Endothelial Cells upon Exposure to Diesel Exhaust Particles

Abstract: Air pollution induces neurodegeneration, including cognitive deficits, neuroinflammation, and disruption of the blood-brain barrier. The mechanisms underlying air pollution-mediated neurodegeneration have not yet been fully elucidated given the limited knowledge on intercellular interactions. A brainon-a-chip platform is presented comprising neurons, glia, and brain endothelial cells (bECs; neuro-glia-vascular, NGV) and diesel exhaust particle (DEP)-induced neurodegeneration is evaluated with a particular focu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 53 publications
1
7
0
Order By: Relevance
“…In addition, diesel exhaust also trigged the highest release of Aβ (blue bar in Figure 4 G), but these aggregates colocalized with neurons rather than the nanoparticles themselves (Figure 4 E; cyan color indicated colocalization of plasma membrane and Aβ signal). Furthermore, diesel exhaust particles caused massive neuronal death across the whole sample, as indicated by the presence of numerous rounded neurons with high membrane label intensity and no axons in Figure 4 E. Such effects were also observed by others in a coculture system (Block et al, 2004; Seo et al, 2023). Interestingly, in the regions where the amount of Aβ deposits was high and diesel exhaust particles colocalized with Aβ deposits, the lengths of neurites were about ten times longer compared to regions with minimal Aβ deposition.…”
Section: Resultssupporting
confidence: 74%
“…In addition, diesel exhaust also trigged the highest release of Aβ (blue bar in Figure 4 G), but these aggregates colocalized with neurons rather than the nanoparticles themselves (Figure 4 E; cyan color indicated colocalization of plasma membrane and Aβ signal). Furthermore, diesel exhaust particles caused massive neuronal death across the whole sample, as indicated by the presence of numerous rounded neurons with high membrane label intensity and no axons in Figure 4 E. Such effects were also observed by others in a coculture system (Block et al, 2004; Seo et al, 2023). Interestingly, in the regions where the amount of Aβ deposits was high and diesel exhaust particles colocalized with Aβ deposits, the lengths of neurites were about ten times longer compared to regions with minimal Aβ deposition.…”
Section: Resultssupporting
confidence: 74%
“…Recent studies reported that exposure of human airway epithelial (Calu-3) cells to pollutants inhibited the cystic fibrosis transmembrane conductance regulator (CFTR), an anion channel important for mucociliary clearance (MCC) (see Glossary) [4] (Figure 2). Other studies in blood-brain barrier (BBB) models also reported that pollutants decreased protein stability of tight junctions (TJ; e.g., zonula occludens-1) and adherence junctions (E-cadherin) (Figure 3) [5]. These findings indicate that environmental pollutants can mediate decline of lung as well as brain function through elevated exacerbation frequency and increased leakage of the BBB, respectively.…”
Section: Environmental Pollutants: Impact On Cellular Homeostasismentioning
confidence: 79%
“…Another source of neurons is neural progenitor cells that can differentiated before loading them in MPS, to study neurovascular phenotypes in Alzheimer's disease, for example [7]. Alternatively, neural progenitor cells can be differentiated on-chip, as was done in study that combined them with microglia and a cylindrical channel lined with brain endothelial cells [25 ▪ ]. The authors used this model to interrogate neuroinflammation originating from exposure to diesel exhaust particles transported through the circulatory system.…”
Section: Organ Specificitymentioning
confidence: 99%